Comparative performance of single and binary metal selenides in dye-sensitized solar cells - Najihah, M.Z.; Saaid, Farish Irfal; Noor, I.M.; Woo, H.J.; Hisam, R.; Winie, Tan (Springer Science and Business Media Deutschland GmbH, 2024)
Iron selenide (FeSe2), cobalt selenide (Co3Se4), and iron cobalt selenide (FeCo2Se4) have been synthesized via a two-step hydrothermal process. The formation of FeSe2, Co3Se4, and FeCo2Se4 has been proven by sample characterization to support their catalytic activity as the counter electrodes for dye-sensitized solar cells (DSSCs). The poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP)/propylene carbonate (PC)/1,2-dimethoxyethane (DME)/1-methyl-3-propyl imidazolium iodide (MPII)/sodium iodide (NaI)/iodine (I2) gel electrolytes were assembled into DSSCs with FeCo2Se4, FeSe2, Co3Se4, or platinum (Pt) as the counter electrode. The DSSC with FeCo2Se4 counter electrode shows an efficiency of 8.55, whereas Pt counter electrode shows an efficiency of 7.06. The highest performance of DSSC achieved with FeCo2Se4 can be attributed to its highest surface area and pore volume. Hence, FeCo2Se4 can be used as a Pt-free counter electrode for high-performance DSSCs.